2007
DOI: 10.1109/tit.2006.887071
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Capacity of OFDM on Rayleigh-Fading Channels

Abstract: Abstract-For a power limited orthogonal frequency-division multiplexing (OFDM) system transmitting a large number N of subcarriers over a Rayleigh-fading channel, the distribution of the instantaneous capacity is shown to be approximately Gaussian. The mean and variance of the approximating distribution are derived. It is also shown that, in the limit as N ! 1, the capacity approaches a constant value equal to the capacity of the infinite-bandwidth Gaussian channel.Index Terms-Channel capacity, orthogonal freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…We finally studied the impact of spatial correlation on SD schemes and we showed that, in order to get an effective gain, correlation between adjacent elements should be kept small when increasing the number of transmit antennas. APPENDIX A PROOFS FOR (7) AND (18) The correlation coefficient ρ m1,m2 in (7) could be computed by developing the equation and by exploiting the WSS-US condition on the channel. However, in the following we propose an alternative fast approach which also permits to easily find (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We finally studied the impact of spatial correlation on SD schemes and we showed that, in order to get an effective gain, correlation between adjacent elements should be kept small when increasing the number of transmit antennas. APPENDIX A PROOFS FOR (7) AND (18) The correlation coefficient ρ m1,m2 in (7) could be computed by developing the equation and by exploiting the WSS-US condition on the channel. However, in the following we propose an alternative fast approach which also permits to easily find (18).…”
Section: Discussionmentioning
confidence: 99%
“…APPENDIX A PROOFS FOR (7) AND (18) The correlation coefficient ρ m1,m2 in (7) could be computed by developing the equation and by exploiting the WSS-US condition on the channel. However, in the following we propose an alternative fast approach which also permits to easily find (18).…”
Section: Discussionmentioning
confidence: 99%
“…2 In contrast to (22), however, the equivalent result from [31] is not expressed in closed form, and it requires the evaluation of infinite series of incomplete gamma functions.…”
Section: A Exact Analysis At All Snrsmentioning
confidence: 99%
“…1, we compare the analytical variance expression (9) , and the SNR is set to 10 dB. In all cases, we see a pre-2 Note that this expression was not explicitly stated in [31]. It can however be obtained by following the derivation of (47) and using [31, eqs.…”
Section: A Exact Analysis At All Snrsmentioning
confidence: 99%
“…For example, similar approaches in [1] and [2] have led to results on the capacity of MIMO OFDM systems and the BER of SISO OFDM systems. Applications of this work can be found in both performance analysis and design.…”
Section: Introductionmentioning
confidence: 99%